Effect of geometry on deformation of anterior implant-supported zirconia frameworks: An in vitro study using digital image correlation. Issue 2 (April 2017) - Calha, Nuno; Messias, Ana; Guerra, Fernando; Martinho, Beatriz; Neto, Maria Augusta; Nicolau, Pedro
Abstract: Purpose: To evaluate the effect of geometry on the displacement and the strain distribution of anterior implant-supported zirconia frameworks under static load using the 3D digital image correlation method. Methods: Two groups (n = 5) of 4-unit zirconia frameworks were produced by CAD/CAM for the implant-abutment assembly. Group 1 comprised five straight configuration frameworks and group 2 consisted of five curved configuration frameworks. Specimens were cemented and submitted to static load up to 200 N. Displacements were captured with two high-speed photographic cameras and analyzed with video correlation system in three spacial axes U, V, W. Statistical analysis was made using the nonparametric Mann–Whitney test. Results: Up to 150 N loads, the vertical displacements (V axis) were statistically higher for curved frameworks (−267.83 ± 23.76 μm), when compared to the straight frameworks (−120.73 ± 36.17 μm) (p = 0.008), as well as anterior displacements in the W transformed axis (589.55 ± 64.51 μm vs 224.29 ± 50.38 μm for the curved and straight frameworks), respectively (p = 0.008). The mean von Mises strains over the surface frameworks were statistically higher for the curved frameworks under any load. Conclusion: Within the limitations of this in vitro study, it is possible to conclude that the geometric configuration influences the deformation of 4-unit anterior frameworks under static load. The higher strain distribution and micro-movements of the curved frameworks reflect less rigidity and increased risk of fractures associated to FPDs.